50 years of rice breeding in Bangladesh: genetic yield trends - Rahman, Niaz Md. Farhat; Malik, Waqas Ahmed; Kabir, Md. Shahjahan; Baten, Md. Azizul; Hossain, Mohammed Ismail; Paul, Debi Narayan Rudra; Ahmed, Rokib; Biswas, Partha Sarathi; Rahman, Md. Chhiddikur; Rahman, Md. Sazzadur; Iftekharuddaula, Khandakar Md.; Hadasch, Steffen; et al. (Springer, 2023)
To assess the efficiency of genetic improvement programs, it is essential to assess the genetic trend in long-term data. The present study estimates the genetic trends for grain yield of rice varieties released between 1970 and 2020 by the Bangladesh Rice Research Institute. The yield of the varieties was assessed from 2001–2002 to 2020–2021 in multi-locations trials. In such a series of trials, yield may increase over time due to (i) genetic improvement (genetic trend) and (ii) improved management or favorable climate change (agronomic/non-genetic trend). In both the winter and monsoon seasons, we observed positive genetic and non-genetic trends. The annual genetic trend for grain yield in both winter and monsoon rice varieties was 0.01 t ha−1, while the non-genetic trend for both seasons was 0.02 t ha−1, corresponding to yearly genetic gains of 0.28% and 0.18% in winter and monsoon seasons, respectively. The overall percentage yield change from 1970 until 2020 for winter rice was 40.96%, of which 13.91% was genetic trend and 27.05% was non-genetic. For the monsoon season, the overall percentage change from 1973 until 2020 was 38.39%, of which genetic and non-genetic increases were 8.36% and 30.03%, respectively. Overall, the contribution of non-genetic trend is larger than genetic trend both for winter and monsoon seasons. These results suggest that limited progress has been made in improving yield in Bangladeshi rice breeding programs over the last 50 years. Breeding programs need to be modernized to deliver sufficient genetic gains in the future to sustain Bangladeshi food security.